Contributions of acidic ions in secondary aerosol to PM2.5 bioreactivity in an urban area. (15th April 2022) - Laiman, Vincent; Hsiao, Ta-Chih; Wang, Yu-Hui; Young, Li-Hao; Chao, How-Ran; Lin, Tang-Huang; Heriyanto, Didik Setyo; Chuang, Hsiao-Chi
Abstract: Adverse human health effects caused by fine particulate matter (PM2.5 ) were reported; however, source-specific PM2.5 and its bioreactivity need to be assessed to understand regional human impacts. The objective of this study was to investigate the contributions of PM2.5 to particle bioreactivity in Taichung City, an urban area of west-central Taiwan. The average mass concentration of PM2.5 was 44.4 μg m −3 from 21 March to April 22, 2018. PM2.5 was identified from six distinct sources using a positive matrix factorization (PMF) model. Secondary aerosols were discovered to be the primary contributor to PM2.5 (25.58%), and were primarily composed of Cl −, NO3 −, EC, NH4 +, and SO4 2− . It was found that approximately 52.20% (23.2 μg m −3 ) of inhaled PM2.5 was deposited in the alveolar region after inhalation in the human lungs according to the multiple-path particle dosimetry (MPPD) model. Therefore, human alveolar epithelial A549 cells were exposed to PM2.5, which significantly reduced lung cell viability, and increased the cytotoxic lactate dehydrogenase (LDH), reactive oxygen species (ROS), and inflammatory interleukin (IL)-6 ( p  < 0.05). Next, we discovered positive correlation between secondary aerosols and ROS production, which was further linked to increases in inorganic ions (Mg 2+, Cl −, NO3 −, and SO4 2− ) ( p  < 0.05). In conclusion, acidic ions from secondary aerosols were positively correlated with ROS production in human alveolar epithelial cells. Our results showed that secondary aerosols could be an important determinant of the deterioration of air quality and human respiratory health in urban areas. Graphical abstract: Image 1 Highlights: Secondary aerosol was the primary source of PM2.5 in Taichung city. More than half of inhaled PM2.5 are able to deposit in the alveolar region. PM2.5 reduced cell viability and increased cytotoxicity, ROS and IL-6 in vitro . Acidic ions from secondary aerosol contributed to ROS production.